Incidence and risk factors of exacerbations among COPD patients in primary health care: APMPOC study - Domènech Cristina; Mezquiriz Xavier; Negrete Antonio; Puigfel Yolanda; Urrea Magalí; Monteagudo Mònica; Montellà Núria; Pera Guillem; Muñoz Laura; Torán Pere; Rodríguez Mar; Borrell Eulàlia; et al. (BMC, 2009)
Abstract Background Worldwide, chronic obstructive pulmonary disease (COPD) is the fourth cause of death. Exacerbations have a negative impact on the prognosis of COPD and the frequency and severity of these episodes are associated with a higher patient mortality. Exacerbations are the first cause of decompensation, hospital admission and death in COPD. The incidence of exacerbations has mainly been estimated in populations of patients with moderate-severe COPD requiring hospital care. However, little is known regarding the epidemiology of exacerbations in patients with less severe COPD forms. It is therefore possible that a high number of these less severe forms of exacerbations are underdiagnosed and may, in the long-term, have certain prognostic importance for the COPD evolution. The aim of this study was to know the incidence and risk factors associated with exacerbations in patients with COPD in primary care. Methods and design A prospective, observational, 3-phase, multicentre study will be performed involving: baseline evaluation, follow up and final evaluation. A total of 685 smokers or ex-smokers from 40 to 80 years of age with COPD, without acute respiratory disease or any other long-term respiratory disease will be randomly selected among the population assigned to 21 primary care centres. The diagnosis of COPD and its severity will be confirmed by spirometry. Information regarding the baseline situation, quality of life and exposure to contaminants or other factors potentially related to exacerbations will be collected. A group of 354 patients with confirmed COPD of varying severity will be followed for one year through monthly telephone calls and daily reporting of symptoms with the aim of detecting all the exacerbations which occur. These patients will be evaluated again at the end of the study and the incidence of exacerbations and associated relative risks will be estimated by negative binomial regression. Discussion The results will be relevant to provide knowledge about natural history of the initial phases of the COPD and the impact and incidence of the exacerbations on the patients with mild-moderate forms of the disease. These data may be important to know the milder forms of exacerbation wich are often silent or very little expressed clinically.